2002
DOI: 10.1016/s0041-0101(01)00288-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitive colorimetric capture ELISAs for Clostridium botulinum neurotoxin serotypes E and F

Abstract: Sensitive and specific enzyme-linked immunosorbent assays (ELISAs) were developed to detect Clostridium botulinum neurotoxin serotypes E (BoNT E) and F (BoNT F) in assay buffer and human serum. The assay is based upon affinity-purified horse polyclonal antibodies directed against the approximately 50 kD C-fragments of each toxin. Standard curves were linear over 0.5-10 ng/ml (BoNT E) or 2-20 ng/ml (BoNT F). Accurate measurements were achieved at 0.5 ng/ml (BoNT E) or 2 ng/ml (BoNT F) in assay buffer and 10% hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 11 publications
1
35
0
2
Order By: Relevance
“…7C, D, and A, respectively). These data agree with previous findings by Poli and coworkers [6] and Szilagyi and coworkers [7]. We also observed that this recognition was different for serotype E (Fig.…”
Section: Comparison Of Pure Bonts With Complex Formssupporting
confidence: 94%
See 2 more Smart Citations
“…7C, D, and A, respectively). These data agree with previous findings by Poli and coworkers [6] and Szilagyi and coworkers [7]. We also observed that this recognition was different for serotype E (Fig.…”
Section: Comparison Of Pure Bonts With Complex Formssupporting
confidence: 94%
“…One problem with such assays is the susceptibility of the assay substrates to nonrelated proteases and the consequent risk of false positives. A variety of antibody-based assays that are both sensitive and serotype specific have been proposed [5][6][7][8]. A drawback with all immunoassays is their inability to distinguish biologically active toxin or toxin fragments from biologically inactive ones.…”
Section: Subject Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment usually takes 5-6 hours to complete, and is significantly faster than mouse lethality assay. ELISAs with an experimental setup analogous to this were reported to have a wide range of sensitivities, depending on the specific antibody and reporter system used, and have been employed for detection of all BoNT serotypes [48,49,50,51]. …”
Section: Elisamentioning
confidence: 99%
“…ELISA methodologies have been successfully employed in the detection and quantification of purified botulinum toxin [49,51,59], in C. botulinum cultures that produce the toxin [60,61,62], in an extensive variety of food samples [52,54,63,64,65] (both contaminated food and food artificially spiked with the toxin), and in clinical samples such as serum [49] and feces [66]. Some foods tend to interfere with ELISAs and decrease their sensitivity; therefore, results should be confirmed by mouse lethality assay.…”
Section: Elisamentioning
confidence: 99%